The production, uses, nutritional and anti-nutritional characteristics of cocoyam as a potential feed ingredient in the tropics: A review - Ukwu, C.P.; Yahaya, A.; Okere, C. (Nigerian Journal of Animal Science, 2023)
Several cocoyam species such as Xanthosoma and Colocasia previously cultivated for their economic and socio-cultural benefits are no longer popularly cultivated by farmers. They grow luxuriantly in the wild at many locations in Southern Nigeria, indicating that they could be harnessed into feed ingredients for animals. Average yields of 9.60 – 37.00 tons/ha per annum is reported for cocoyam root, while cocoyam foliage yield could be as high as 128 – 370 tons/ha/year. Cocoyam tuber has superior nutritional value over other major roots and tuber crops like yam and cassava in terms of digestible starch, proteins, vitamins and mineral compositions. Crude protein range of 2.01 – 10.10%, and metabolizable energy (2588.44 – 3902.70 Kcal/kg) have been reported. The leaves are high in moisture content, and rich in proteins, vitamins and minerals. The major phytochemical and anti-nutrients in cocoyam roots in mg/kg were alkaloids (0.19 – 1.97), oxalates (0.01 – 30.28), phenols (0.012 – 270.49), tannins (0.20 – 1066.19), and trypsin inhibitor (1.37 – 632.02). The leaves contain significant levels of tannin (32.15mg/100g), flavonoids (62.62mg/100g), phenols (6.28mg/100g), trypsin inhibitor (1069.43mg/kg), and alkaloids (2.40mg/kg) among others. In spite of the anti-nutrient contents of cocoyam which limit its use in livestock feed, it is concluded that when properly processed, cocoyam root meal could be adopted as alternative energy source, while the processed leaf meal could serve as alternative protein source for livestock, and poultry feeding.